European Concerted Action on Anticoagulation (ECAA): International Normalized Ratio Variability of CoaguChek and TAS Point-of-Care Testing Whole Blood Prothrombin Time Monitors - Poller, L.; Keown, M.; Chauhan, N.; Shiach, C.; van den Besselaar, A. M. H. P.; Tripodi, A.; Jespersen, J. (Thrombosis and Haemostasis, 2002)
The object was to assess the variability in displayed International Normalised Ratio (INR) between monitors of the same manufacture using whole blood samples from the same subjects. Two brands of monitor, CoaguChek Mini and the TAS PT-NC were tested.14 instruments of each brand were tested on the same day at the same laboratory by the same operator using identical blood samples to avoid between-centre differences in samples and operator technique. Whole blood samples from two normal donors and four coumarintreated patients were tested to assess between-instrument variability of INR.Results have been coded. There was a much wider dispersion of INR on Brand B than on Brand A. One Brand A instrument failed to give a result with one of the two whole blood samples from one patient. One Brand B monitor gave an aberrant result with one of the samples from a normal subject.On both brands of monitor, INR variability appeared to be due mainly to duplication differences rather than between-instrument variability on both normal and coumarin whole blood samples.
Keywords: POCT monitors; prothrombin time; International Normalised Ratio; between-instrument variability; within-instrument variability